2016
DOI: 10.1093/heapro/daw025
|View full text |Cite
|
Sign up to set email alerts
|

Best practices for community gardening in a US–Mexico border community

Abstract: Minority communities such as those on the US-Mexico border are placed at disproportionate high risk for child and adult obesity, diabetes and cardiovascular diseases. A built environment characterized by an arid desert climate, lack of access to healthy foods, barriers to increasing physical activity, cultural and community norms which deter healthy eating and sustainable food production, shape obesity-related health disparities in these communities. Three pilot community gardens (implemented by two local gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Three of these studies were conducted in the United States, with one each from Canada, Japan, Portugal and the Netherlands. All were cross-sectional in design and sample sizes ranged from 25 [40] to 500 [39]. Findings were generally positive for gardening and community-related outcomes.…”
Section: Community Outcomesmentioning
confidence: 99%
“…Three of these studies were conducted in the United States, with one each from Canada, Japan, Portugal and the Netherlands. All were cross-sectional in design and sample sizes ranged from 25 [40] to 500 [39]. Findings were generally positive for gardening and community-related outcomes.…”
Section: Community Outcomesmentioning
confidence: 99%
“…Studies frequently report on educational benefits and skill development (41). This includes learning about nature and the environment, urban agriculture, and nutrition, or developing skills, both in terms of interpersonal skills, such as problem solving, e.g., [106], and more practical skills, e.g., [100]. An improved connection to nature following participatory urban green space creation is found in 26 studies.…”
Section: Effects Of Participation In Green Space Creation On Other Ou...mentioning
confidence: 99%
“…This includes five quantitative studies that report increased nature connectedness or an increased environmental identity and 21 studies that qualitatively note better connections or relations to nature, as well as participants describing that they feel more comfortable in nature, have more fun [43,126], or feel embedded in nature [118]. Additionally, six studies note that participants reported increased pro-environmental behaviors and attitudes [76,139,147], adopted more sustainable lifestyles [97,117], or cared more about the environment [106]. Participants in twelve studies attributed benefits to the environment to be an outcome of their participatory green space activities, such as an improved appearance of public spaces, an improvement to the natural environment [102,152], and benefits for biodiversity and local wildlife [53,113,116].…”
Section: Effects Of Participation In Green Space Creation On Other Ou...mentioning
confidence: 99%
“…Research literature has provided a positive relationship between the supply of facilities and various forms of social processes. For instance, community gardens are in itself a place where participants can build up new friendship over an interest of gardening, share their produces with others, spend more time gardening with their families, and meet their neighbors, which all contribute to improved social ties and social support (Hale et al, 2011;Mangadu, Kelly, Orezzoli, Gallegos, & Matharasi, 2017;Noone & Jenkins, 2017). Moreover, the availability of benches, tables, and playground facilities in community gardens forms a social friendly area where individuals can socialize with each other (Kingsley & Townsend, 2006).…”
Section: Physical Characteristicsmentioning
confidence: 99%